Nuclear physics with unstable ions at storage rings - Bosch, Fritz; Litvinov, Yuri A.; Stöhlker, Thomas (Progress in particle and nuclear physics, 2013)
During the last two decades, ion storage-cooler rings have been proven as powerful devices for addressing precision experiments in the realm of atomic physics, nuclear physics and nuclear astrophysics. Most important, in particular for stored unstable nuclides, is the unrivalled capability of ion cooler-rings to generate brilliant beams of highest phase-space density owing to sophisticated cooling techniques, and to store them for extended periods of time by preserving their charge state. This report focuses on nuclear physics and nuclear astrophysics experiments with in-flight produced exotic ions that were injected into storage-cooler rings. Those experiments were conducted within the last decade mainly at the only operating facilities that are capable to provide and to store exotic ions, namely the ESR in Darmstadt, Germany and the CSRe-ring in Lanzhou, China. The majority of nuclear physics experiments performed at these equipments concerns ground-state properties of nuclei far from stability, such as masses and lifetimes. The rich harvest of these measurements is presented. In particular it is shown that storage-cooler rings are ideal, if not the only, devices where two-body beta decays of exotic highly-charged ions, such as bound-state beta decay and orbital electron capture, can be studied in every detail, based on “single-ion decay spectroscopy”. Furthermore, experiments at the border between atomic and nuclear physics are discussed which render valuable information on nuclear properties by exploiting one of the most precise tools of atomic spectroscopy on stored ions, the “dielectronic recombination”. Ion storage rings with cooled exotic beams and equipped with thin internal gas targets deliver also unrivalled opportunities for addressing with highest precision key reactions in the fields of nuclear astrophysics and nuclear structure. First very promising experiments exploring the potential of ion cooler-rings in this realm have been already conducted. However, in view of the small nuclear cross sections, many of fervently desired experiments in this field will still suffer from the insufficient number of exotic ions that can be delivered and stored at the time being. The realistic hope on a breakthrough in this field is based on the ion storage rings to come, with their estimated improvements in the intensity of exotic ion beams by many orders of magnitude.